Effects of scaffold microstructure and low intensity pulsed ultrasound on chondrogenic differentiation of human mesenchymal stem cells. Issue 2 (22nd November 2017) - Aliabouzar, Mitra; Lee, Se‐jun; Zhou, Xuan; Zhang, Grace Lijjie; Sarkar, Kausik
Abstract: The effects of low intensity pulsed ultrasound (LIPUS) on proliferation and chondrogenic differentiation of human mesenchymal stem cells (hMSCs) seeded on 3D printed poly‐(ethylene glycol)‐diacrylate (PEG‐DA) scaffolds with varying pore geometries (square and hexagonal channels) were investigated. The scaffold with square pores resulted in higher hMSC growth and chondrogenic differentiation than a solid or a hexagonally porous scaffold. The optimal LIPUS parameters at 1.5 MHz were found to be 100 mW/cm 2 and 20% duty cycle. LIPUS stimulation increased proliferation by up to 60% after 24 hr. For chondrogenesis, we evaluated key cartilage biomarkers abundant in cartilage tissue; glycosaminoglycan (GAG), type II collagen and total collagen. LIPUS stimulation enhanced GAG synthesis up to 16% and 11% for scaffolds with square and hexagonal patterns, respectively, after 2 weeks. Additionally, type II collagen production increased by 60% and 40% for the same patterns, respectively under LIPUS stimulation after 3 weeks. These results suggest that LIPUS stimulation, which has already been approved by FDA for treatment of bone fracture, could be a highly efficient tool for tissue engineering in combination with 3D printing and hMSCs to regenerate damaged cartilage tissues. Abstract : The present investigation suggests that low intensity pulsed ultrasound (LIPUS), which is non‐invasive, efficient and cost‐effective, combined with 3D‐printing techniques can be an invaluable tool for cartilage tissue engineering using human mesenchymal stem cells (hMSC) to regenerate damaged cartilages. Porous scaffolds were 3D printed using poly‐(ethylene glycol)‐diacrylate as the bioink by a novel stereolithography‐based technique. The authors have thoroughly evaluated the proliferation as well as chondrogenic differentiation of hMSCs seeded on 3D printed scaffolds with varying pore channels under optimized LIPUS treatment.